2022
DOI: 10.3390/ijms232113361
|View full text |Cite
|
Sign up to set email alerts
|

Signal Peptide Variants in Inherited Retinal Diseases: A Multi-Institutional Case Series

Abstract: Signal peptide (SP) mutations are an infrequent cause of inherited retinal diseases (IRDs). We report the genes currently associated with an IRD that possess an SP sequence and assess the prevalence of these variants in a multi-institutional retrospective review of clinical genetic testing records. The online databases, RetNet and UniProt, were used to determine which IRD genes possess a SP. A multicenter retrospective review was performed to retrieve cases of patients with a confirmed diagnosis of an IRD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Translocation from the cytoplasm into the ER requires a functional amino terminal signal peptide, which needs to efficiently interact with the Sec61 translocon complex, open the channel to initiate translocation, and be available for the proper cleavage by the peptidase. Therefore, mutations that disrupt the hydrophobic core of the SP have a deleterious effect on translocation efficiency in vivo and in vitro (Jimenez et al, 2022). Here, we found that the translocation deficient ppαF mutant, in which the alanine 13 located on the hydrophobic core is replaced by a glutamic acid, significantly impaired the strength and presumably the specificity of the interaction between the signal peptide and the Sec61 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation from the cytoplasm into the ER requires a functional amino terminal signal peptide, which needs to efficiently interact with the Sec61 translocon complex, open the channel to initiate translocation, and be available for the proper cleavage by the peptidase. Therefore, mutations that disrupt the hydrophobic core of the SP have a deleterious effect on translocation efficiency in vivo and in vitro (Jimenez et al, 2022). Here, we found that the translocation deficient ppαF mutant, in which the alanine 13 located on the hydrophobic core is replaced by a glutamic acid, significantly impaired the strength and presumably the specificity of the interaction between the signal peptide and the Sec61 complex.…”
Section: Discussionmentioning
confidence: 99%